Faktor yang Memengaruhi Episode Transfusi Packed Red Cell (PRC) pada Anak dengan Keganasan - PURWANTO, DIAN A.P; MULATSIH, SRI; TRIYONO, TEGUH (Indonesian Journal of Cancer, 2017)
ABSTRACTPRC transfusion is an adjuvant therapy frequently used in children with malignancy. There are some factors affecting transfusion episodes. For rational use of PRC must consider these factors. Objective: To find factors affecting transfusion episodes in children with malignancy. This retrospective cohort study evaluated children with malignancy between January 1 and December 31, 2015 who were admitted to Sardjito hospital. Patients were receiving therapy dan PRC transfusion during the four months following cancer diagnosis. Those with incomplete data or renal failure were excluded. The influence of these factors were analyzed with Chi-square or Fisherâs exact and Kolmogorov-Smirnov when iligible, and the most influential factor were analyzed by logistic regression. Out of 123 subjects receiving a PRC transfusion, 56 (45,5%) subjects received a PRC transfusion more than one times episodes. Higher episodes of transfusion were observed for patients whose bleeding (RR 6.940 (95%CI 2.563 to 18.790). Lower episodes of transfusion were observed for patients receiving transfusion previously and hematological malignancies, but the result were not significant (RR 0,524 (IK95% 0,057 â 4,852) and 0,464 (IK 95% 0,140 â 1,540) respectively). Bleeding is factor affecting transfusion episodes of PRC in children with malignancy.ABSTRAKTransfusi PRC merupakan terapi adjuvant yang sering digunakan pada anak dengan keganasan. Terdapat beberapa faktor yang memengaruhi episode transfusi sehingga penggunaan PRC rasional harus mempertimbangkan faktor tersebut. Penelitian ini bertujuan mengetahui faktor yang memengaruhi episode transfusi PRC pada anak dengan keganasan. Penelitian kohort retrospektif pada anak (0 â18 tahun) yang dirawat di RSUP Dr. Sardjito dengan penyakit keganasan yang telah terdiagnosis selama empat bulan dan mendapat terapi serta transfusi PRC sejak 1 Januari â 31 Desember 2015. Register tidak lengkap atau dengan gagal ginjal dieksklusi. Pengaruh faktorâ faktor tersebut dianalisis dengan uji Chi-square atau uji Fisher serta Kolmogorov-Smirnov bila tidak memenuhi syarat, dan faktor yang paling berpengaruh dianalisis dengan uji logistic regression. Dari 123 subjek, 56 subjek dengan episode transfusi PRC > 1 kali. Keganasan hematologi, riwayat transfusi, dan perdarahan memengaruhi episode transfusi PRC > 1 kali. Analisis multivariat didapatkan perdarahan memengaruhi episode transfusi PRC > 1 kali (RR 6,940 (IK95% 2,563 â 18,790), namun riwayat transfusi dan keganasan hematologi tidak bermakna dengan nilai RR secara berturut-turut 0,524 (IK95% 0,057 â 4,852) dan 0,464 (IK 95% 0,140 â 1,540). Penelitian ini menyimpulkan bahwa perdarahan merupakan faktor yang memengaruhi episode transfusi PRC pada anak dengan keganasan.Â